Plunging Airfoil Motion: Effects of Unequal Ascending and Descending Velocities - Rodrigues, Diana Carvalho (2020)
Biomimetics is a multidisciplinary area of science studying the development of new technologies, whose source of inspiration is Nature and has given rise to new technologies inspired by biological solutions at macro and nanoscales. Successive work carried out by researchers in this field revealed that flapping wings offers not only benefits but unique aerodynamic advantages when compared to the traditional fixed-wings, especially when approaching small scales. This work presents an experimental study concerning the created vortical structures of a plunging NACA0012 airfoil subjected to an asymmetrical motion at a Reynolds number of 1500 with different reduced frequencies and nondimensional amplitudes. The asymmetric motion studied was based on a velocity triangular wave with special focus in a plunging cycle asymmetry of 75%. Over its plunging motion, the unequal ascending and descending velocities revealed that the airfoil can produce both thrust and lift simultaneously. Leading-Edge Vortex (LEV) formation and its convection over the upper surface of the airfoil was seen as a possible power reduction mechanism which could be a way to improve propulsive and energy extraction efficiencies.